Philosophy Bridging the World Religions
IX, 259 p.
Keywords: Religions are the largest communities of the global society and claim, at least in the cases of Islam and Christianity, to be universal interpretations of life and orders of existence. With the globalization of the world economy and the unity of the global society in the Internet, they gain unprecedented access to the entire human race through modern means of communication. At the same time, this globalization brings religions into conflict with one another in their claims to universal validity. How can the conflict of religions be defused? The speculative, philosophical method of dealing with a religion is a way to present one's own religious convictions in the medium of philosophy and rational discourse. The philosophical approach to religion can serve as the basis of the conversation of the world religions, without dissolving their truth claims. It can reduce dogmatic claims and contribute to overcoming fundamentalism. Philosophy builds bridges between religions. The series A Discourse of the World Religions presents with this volume the fifth and last of the EXPO-Discourses of the World Religions, which took place near the end of the World Exposition EXPO 2000 in Hannover, Germany. The five EXPO-Discourses were held before and during the World Exposition EXPO 2000 in Hannover with the objective of a philosophical-theological dialogue of religions about central themes of their teachings. The series aims at a deeper understanding of the similarities and differences between Hinduism, Buddhism, Judaism, Christianity, and Islam in their theological and philosophical propositions. It sees in philosophy a bridge between the religions and a means to overcome religious hostility and fundamentalism and to further the dialogue of the religions.